(untitled) (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2024)
This article investigates the application of Optical Character Recognition (OCR) techniques for accurately identifying the Latin Braille alphabet in the Uzbek language, specifically designed to support individuals with visual impairments. The recognition process integrates a variety of image processing and analysis approaches to enhance the precision of character detection. Particular focus was placed on implementing adaptive thresholding techniques to handle variations in image lighting and contrast. Additionally, the method incorporates the determination of text inclination angles, which is crucial for correcting skewed input images and improving the overall accuracy of Braille text recognition.